História e leitura musicalizada : afinidade eletiva entre movimento pelos direitos civis, blues e o voodoo (1960-1970) - Kawaguchi, Kenny Kendy (2024)
This investigation focuses on the racial conflict between African Americans and the segregation in the United States that occurred in the central and southern regions of North America, a geographical area delimited by the Mississippi River. The research spans from 1960 to 1970, a period during which different expressions of the past are in contention. One aspect of the past claims ancestry, allowing its cultural influence to flow through the social, spiritual, and musical aspects of African American life. This stance contributed to the initial achievements of civil rights during the 1960s. The opposing, more conservative aspect of history vehemently opposes the advancements made by African Americans and other social minorities, anchoring itself in racial segregation as an ideology, perpetuating the vices of the colonial era through criminal acts and cementing its prejudices in the form of Jim Crow laws (1877-1964). Our investigation considers the 1960s as the pinnacle of the Civil Rights Movement. During this period, two musical sources are the focus of our research. The first is the bluesman/songwriter Son House (1902–1988) with his delta blues expressed thematically in compositional acts such as worksongs, as seen in "Grinnin’ in your face," released in 1965. The second piece is from the bluesman Muddy Waters (1913–1983), who thematically ritualizes a praise through his song "My John The Conqueror Root," released in 1964. To analyze these sources, we carried out a critique of musicalized reading, treating the documentary source through its musical aspects. This method of sound reading is supported by the theory of song semiotics and aligns with the historian's craft. Our investigation aims to open the discussion on method through its practice, applying it during the Civil Rights era and its relationship with delta blues and voodoo spirituality. We consider the three aspects — politics, spirituality, and music — as elective affinities, a concept that serves as a tool to consider the aspect of ancestral past as the convergence point of these social phenomena. We argue that the method of musicalized reading can help investigate musical codes imprinted in specific historical contexts through qualitative analysis of song texts (passional, thematic, and figurative), therefore, it is in our interest for historiography to address musical documents within its thematic field, making the debate surrounding its application accessible, thus, alleviating history's discomfort in approaching the realm of sounds and their meanings.